Vinasse from sugarcane bagasse (hemicellulose) acid hydrolysate and molasses supplemented: biodegradability and toxicity - Candido, João Paulo [UNESP]; Almeida, Éryka Costa; de Oliveira Leite, Dilza Nalin [UNESP]; Brienzo, Michel [UNESP]; de Franceschi de Angelis, Dejanira [UNESP] (Springer Nature, 2021)
Vinasse sugarcane is a valuable byproduct of the ethanol production process, presenting a perspective of volume increase with the development of second generation ethanol (2GE). However, this byproduct needs new methods of treatment and management for sustainability. Besides that, 2GE vinasse can be associated with some compounds (such as furan derivatives, phenolic compounds and organic acids), depending on the process used to solubilize hemicellulose, which could compromise vinasse destination or utilization. For this reason, detoxification methods of the hemicellulosic hydrolysates, from which vinasse is obtained in subsequent steps, are crucial. This study aimed to investigate whether the biological detoxification of vinasse from 2GE presents a difference concerning the microbial activity of biodegradation and toxicity when compared to vinasse without the detoxification process. Two vinasses (1, before; and 2, after detoxification) from fermented sugarcane bagasse (hemicellulose fraction) acid hydrolysate (supplemented with its molasses), under different concentrations: 2.5; 5 e 10% were evaluated. Their physicochemical characterization, biodegradation microbial activity (through Bartha and Pramer respirometric method, with total count of heterotrophic bacteria and fungi), and toxicity evaluation (through bioassays with Lactuca sativa at concentraction: 2.5; 5 e 10% and Daphnia similis to 1.5; 2.5; 3.5; 4.5; 5 and 10%) were performed. The results indicated high mineral and organic matter, which under a specific circumstance (2.5% of soil conditioning), enabled high efficiency in biodegradation (>80%). The bioassays with L. sativa signaled negative effect for radicular growth when the vinasses were applied at a concentration of 5 and 10% (sublethal effect and delayed root growth). Acute effects were observed in D. similis, with 50% of immobilization, at concentrations of 4.13% and 4.74% for vinasses 1 and 2, respectively. These results indicate that the biodegradation of vinasse from sugarcane bagasse acid hydrolysate occurs at relatively low levels (up to 5%) and suggests that higher concentrations (≥10%) may impair the growth of soil-associated microorganisms.
Keywords: Acid hydrolysate; Hemicellulosic ethanol; Lignocellulose materials; Respirometric degradation